South East Europe Regular Economic Report No. 5 : First Insights into Promoting Shared Prosperity in South East Europe - World Bank (Washington, DC, 2014)
Long-term economic growth is the key driver for increasing the economic wellbeing of the population, but the pattern and the incidence of growth also matter. Economic growth narrowly based on certain enclave sectors or benefitting small groups is neither socially stable nor sustainable. Along these lines, the World Bank recently revised its institutional strategy, establishing two goals, namely: (i) ending extreme global poverty, the traditional goal of the institution, by reducing the percentage of people living on less than $1.25 a day globally to 3 percent by 2030, and (ii) promoting shared prosperity by fostering income growth of the bottom 40 percent of the population. Furthermore, as an overarching condition, the World Bank aims to achieve those goals in a way that is environmentally, economically and socially sustainable to ensure that welfare of the population is not increased at the expense of future generations or specific groups in society. This paper presents first insights into shared prosperity in SEE6 countries. First, it looks at the incidence of growth in SEE6 in the context of the Europe and Central Asia region to determine whether economic growth knowledge gaps are discussed in the paper. The analysis is limited by the availability of micro-data and thus covers different periods by country, depending on each one's most recent data available. Unless otherwise noted, periods refer to: Albania (2008-2012), Bosnia and Herzegovina (2007), Kosovo (2006-2011), FYR Macedonia (2003-2008), Montenegro (2006-2011) and Serbia (2007-2010).